2019
DOI: 10.1021/acs.macromol.9b01879
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Conductivity via Homopolymer-Rich Pathways in Block Polymer-Blended Electrolytes

Abstract: The optimization of ionic conductivity and lithium-ion battery stability can be achieved by independently tuning the ion transport and mechanical robustness of block polymer (BP) electrolytes. However, the ionic conductivity of BP electrolytes is inherently limited by the covalent attachment of the ionically conductive block to the mechanically robust block, among other factors. Herein, the BP electrolyte polystyrene-block-poly(oligo-oxyethylene methacrylate) [PS-b-POEM] was blended with POEM homopolymers of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 57 publications
1
57
0
Order By: Relevance
“…A more plausible explanation is that the volume fraction of conducting material that should be considered is less than the total volume fraction of PEO-LiTFSI in the system. It has been previously suggested that PEO-LiTFSI in SEO exhibits a lower ionic mobility only locally near the polystyrene interface, while far from the interface, the PEO within the block copolymer should behave identically to the homopolymer PEO. , Here, we consider a two-layer model in which the PEO domain is partitioned into an inactive region near the domain interface with no contribution to the conductivity and an active region, which exhibits the same conductivity as homopolymer PEO at the same salt concentration. Using the two-layer model, we can define an “active volume fraction” (ϕ active ) of PEO within the block copolymer that contributes to the measured conductivity given by The inactive PEO phase (ϕ inactive ) in the SEO has a corresponding volume fraction given by We report ϕ active and ϕ inactive for each salt concentration in Table , where the value of ϕ active is derived from the average value of σ n across the measured temperature range.…”
Section: Resultsmentioning
confidence: 99%
“…A more plausible explanation is that the volume fraction of conducting material that should be considered is less than the total volume fraction of PEO-LiTFSI in the system. It has been previously suggested that PEO-LiTFSI in SEO exhibits a lower ionic mobility only locally near the polystyrene interface, while far from the interface, the PEO within the block copolymer should behave identically to the homopolymer PEO. , Here, we consider a two-layer model in which the PEO domain is partitioned into an inactive region near the domain interface with no contribution to the conductivity and an active region, which exhibits the same conductivity as homopolymer PEO at the same salt concentration. Using the two-layer model, we can define an “active volume fraction” (ϕ active ) of PEO within the block copolymer that contributes to the measured conductivity given by The inactive PEO phase (ϕ inactive ) in the SEO has a corresponding volume fraction given by We report ϕ active and ϕ inactive for each salt concentration in Table , where the value of ϕ active is derived from the average value of σ n across the measured temperature range.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] Moreover, the preference of ion transport along interface rather than entering interior of ceramics, was further proved by the high conductivity under large volume fraction of interfaces. 19 In addition, new twists ranging from copolymerization, [20][21][22] chain network, 23,24 polymer blend, 25 and nano-porous structure, 19,26 to ionic side group 27 and plasticizer, 28,29 bring promising improvements. Releasing the potential of solid composite electrolytes requires mastering mechanism of ion transport in such materials.…”
Section: Introductionmentioning
confidence: 99%
“…15,20 Since such high molar mass materials are difficult to synthesize and process, other investigations focused on the properties of different block polymer architectures including triblock, 21,22 star, 23 brush, 24,25 and hyperbranched materials. 26 More recently, Morris et al 27 and Xie et al 28 investigated microphase separated block polymer/homopolymer blends to further improve these "dry" electrolyte conductivities. Collectively, these studies establish that chain architecture, the presence of PEO homopolymer, and selected polymer end-group functionalities 29 influence the observed conductivities.…”
Section: ■ Introductionmentioning
confidence: 99%